Mental flexibility among kindergarten teachers (Journal of the College of Basic Education, 2024)
The research aims to identify:1- Mental flexibility among kindergarten teachers.2- Mental flexibility among married and unmarried kindergarten teachers.3- Mental flexibility among kindergarten teachers according to years of service.